VOCATIONAL TECHNICAL EDUCATION: A VIABLE TOOL FOR NATIONAL DEVELOPMENT IN NIGERIA - Samuel, Owodunni A.; Mohammed, Hassan A.; Abdulrahman, Sani; Dantala, Nakaka; Nelson, Oguntuyi A. (Sokoto Educational Review, 2014)
Vocational Technical Education (VTE) systems play a crucial role in the social and economic development of a nation. Vocational and technical education a multifaceted, multi-disciplinary and pragmatic field of study, is aimed at equipping the individuals with requisite vocational and technical education literacy skills, which will enhance their relevance and functionality in the society. As a result, it plays a vital and indispensable role in the development of society. This paper, therefore, examines the concept of the development of vocational and technical education in Nigeria, its significance and role with regards to the Economic and Technology development in Nigeria, the concept of Vocational-Technical Education and Training (VTET), VTE and National Development. Other issues discussed are VTET for self-reliance and National Development, the administration of VTE in Nigeria, the challenges ahead as well as possible and suggestions for moving VTE forward with enhanced effectiveness for the benefit of the nation and incoming generations.